Synthetic Nanocelluloses Fluorescently Responsible to Enzymatic Degradation - Shirokawa, Koichi (Langmuir : the ACS journal of surfaces and colloids, 2023)
Crystalline assemblies of cellulose and cellulose derivatives that can be synthetically produced by in vitro enzymatic reactions in a bottom-up manner have attracted increasing attention as chemically designable functional nanomaterials (e.g., synthetic nanocelluloses). In this study, we demonstrate the preparation and characterization of alkyl β-celluloside assemblies loaded with fluorescent molecules, which are fluorescently responsible to the enzymatic degradation of the cellulose moieties. The fluorescent properties are afforded to the assemblies by their bilayer-structured nanosheet morphologies realized through the uptake of environmentally responsive fluorescent molecules (namely, Nile Red (NR)). Incubation of the NR-loaded n-octyl β-celluloside (CEL-C8) assembly with cellulase resulted in decreases in the fluorescence intensities. This suggests that NR molecules were released into the aqueous phase through enzymatic degradation of the cellulose moieties of CEL-C8 molecules in the assembly. The fluorescence decrease rates were clearly dependent on the concentration and source of cellulase. Fluorescence decreases through enzymatic degradation were again observed in the presence of contaminant proteins. These observations revealed the high potential of alkyl β-celluloside assemblies loaded with fluorescent molecules as fluorescently responsible cellulase substrates for cellulase detection assays by simply measuring changes in the fluorescence intensities. Moreover, the assemblies were revealed as carriers for the controlled release of loaded molecules triggered by enzymatic degradation